Sociological Research of the Adherence of Medical Students to Employment by Specialty Received at a University - G. M. Gaidarov (Scientific Сentre for Family Health and Human Reproduction Problems, 2019)
Background. A significant number of medical students refuse to work on a specialty obtained in medical universities after its completion or during the first years of professional activity.Purpose of the study: to conduct a sociological study of the adherence of students of a medical university to employment in a specialty received at a university, as well as factors of its motivation.Methods. A sociological survey of graduate students of ISMU was conducted using specially designed questionnaires.Results. It was revealed that more than 5 % of students do not plan to work on the received specialty after graduating from a medical university. Only every fourth respondent after graduation is going to return to his place of permanent residence, one of four intends not to return, and half have not yet decided on the choice of a further place of work and residence. Work with undergraduates about bringing them to the territory of the initial residence is organized by the administration of municipal entities and medical organizations poorly. Meanwhile, the requirements of graduates presented to a potential employer in terms of the level of wages and the creation of conditions for residence and professional activity are not overstated.Conclusion. Working with graduates and taking specific steps to implement their requirements is the most logical option for joint activities of medical universities, health authorities, administrations of medical organizations and local self-government bodies to create favorable conditions for securing young professionals in their chosen field of activity.